2012
DOI: 10.1186/1751-0759-6-16
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Lactobacillus brevis KB290 against irritable bowel syndrome: a placebo-controlled double-blind crossover trial

Abstract: BackgroundIrritable bowel syndrome (IBS) is a functional disorder of the digestive tract that causes chronic abdominal symptoms. We evaluated the effects of Lactobacillus brevis KB290 (KB290), which has been demonstrated to be effective at improving bowel movements and the composition of intestinal microflora, on IBS symptoms.MethodsWe performed a placebo control double-blind cross matched trial. Thirty-five males and females (aged 6 years and above) who had been diagnosed with IBS according to the Rome III cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…37,52,56, Four studies employed a cross-over design, 52,56,90,105 which is frequently used for motivational purposes (patients are easier to recruit when they are offered an effective treatment, at least for a part of the trial). However, they are difficult to evaluate since the assumption that the data in both periods is equal and can be merged may be distorted by unblinding and conditioning effects.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…37,52,56, Four studies employed a cross-over design, 52,56,90,105 which is frequently used for motivational purposes (patients are easier to recruit when they are offered an effective treatment, at least for a part of the trial). However, they are difficult to evaluate since the assumption that the data in both periods is equal and can be merged may be distorted by unblinding and conditioning effects.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Other lactobacilli strains were used only in single trials, such as Lactobacillus brevi, 90 L. acidophilus, 56,100 Lactobacillus reuteri, 103 Lactobacillus rhamnosus GG, 107 and Lactobacillus casei (CLR35).…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…We recently showed that some plant-derived strains have high bile tolerance [19]. Lactobacillus brevis KB290 isolated from suguki, a traditional fermented vegetable product from the Kyoto region of Japan, has several probiotic activities, including stimulation of immune function [7,21,38] and improvement of gut health [27,29]. Strain KB290 can tolerate artificial digestive juice and bile salts because of its cell-bound exopolysaccharide (EPS) [34] and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…KB290 has been found to tolerate gastrointestinal juices, stimulate immune function [13][15], and improve gut health [13][15]. Moreover, KB290 has a strong tendency to aggregate in broth medium, which may be a desirable property that allows for co-aggregation with pathogenic bacteria, and it colonizes and immunomodulates colonic mucosa [16][21].…”
Section: Introductionmentioning
confidence: 99%